Production of a broad-specificity monoclonal antibody and application as a receptor to detection amatoxins in mushroom. (September 2017) - He, Kuo; Mao, Qingwen; Zang, Xiuyuan; Zhang, Yanyu; Li, Hui; Zhang, Donghao
Abstract: In this study, we report the production of a monoclonal broad-specificity monoclonal antibody (mAb) specific for amatoxins and development of an indirect competitive immunoassay for detection of amatoxins in mushroom samples. In the assay, the complete antigen (α-amanitin-OVA) was used as coating antigen, and amatoxins as competitor competes with coating antigen to bind with mAb. Using this approach, The half-maximum inhibition concentrations (IC50 ) of α-amanitin, β-amanitin and γ-amanitin, and limits of detection (LODs, IC15 ) were 66.3, 97.4, 163.1 ng/mL and 0.91, 0.98, 0.89 ng/mL, respectively. The LODs for α-amanitin, β-amanitin and γ-amanitin in mushroom samples were 4.55, 4.9, and 4.45 ng/mL. The spiked results were also confirmed by HPLC, which showed a good correlation (R 2  = 0.996) between the two methods. The results indicated that the developed assay was reliable and suitable for the detection of amatoxins in mushroom samples.